Gliomatosis presenting as a relative pupil-sparing third nerve palsy in a hypertensive diabetic. (6th December 2010) - Sheikh, U; Price, CJS; Gutowski, NJ
Abstract : We present an unusual case of a 41-year-old male patient who presented to the ophthalmology department giving a 3-month history of right sided ptosis, weight loss, diplopia and headache. Clinical examination revealed a right sided relative pupil-sparing third nerve palsy. MRI scan of brain showed thickening of both third nerves. Further investigations revealed a glioblastoma.